Internet addiction and its harmful effect on adolescents. A perspective on prevention. - Viteri-Oñate, Héctor; Cazar-García, Juan; Fuenmayor-González , Luis; Andrade-Mafla, Jaime; Freire-Erazo, Ana; Guayasamín-Tipanta, Glenda (Revista de la Facultad de Ciencias Médicas (Quito), 2023)
The emergence of the Internet has promoted and changed various activities, both political and educational, economic, social, and cultural, but despite its abundant resources for knowledge, it has also produced a negative impact on people's behaviors and thoughts, which has led them to addiction. Adolescence constitutes a vulnerable period; it is the transition between childhood and youth, and Internet addiction can be a consequence of its state of emotional transition with biological and psychological consequences. For its prevention, the collaboration of parents, teachers, and adolescents is necessary through internal regulations in the family and educational sphere and of the states through the creation of laws and regulations that contain the levels of increase in Internet addiction. The objective of this review is to establish preventive measures for Internet addiction in adolescents. To achieve this, a literature review of the studies found in the PubMed, ScienceDirect, and Redalyc databases was carried out, following the PRISMA methodology. 27 studies were found, 17 referring to the harmful effects on health and 10 studies on preventing Internet addiction. From the selected articles, it was evident that the prevention of Internet addiction in adolescents is based on the intervention of states through the implementation of laws and regulations for safe online access, of the educational system through digital education for students, parents and teachers, family intervention by establishing strict rules to direct the behavior of adolescents and at an individual level with the improvement of emotional skills, training in techniques to control impulsivity, self-control and the consolidation of sports practices.